LEGAL CERTAINTY FOR INVESTORS POST DECISION OF THE MK NO.91/PUUXVIII/2020 TOWARD ECONOMIC RECOVERY IN INDONESIA - Setiawan, Ikhsan; Mahdewi, Risa (Sriwijaya Crimen and Legal Studies, 2023)
Investment can be an important instrument for Indonesia because natural resources are abundant, but only a small portion can be explored by Indonesian citizens because they are constrained by not having large capital. Exploration requires large funds; therefore, the government brings foreign investors to Indonesia. Investors need to be a very important part of realizing the nation's ideals for the welfare of the people, as stated in the preamble of the 1945 Constitution. Investment can be put to good use to enhance economic development and become one of the instruments to increase the nation's national income. For this reason, after the decision of the Constitutional Court No. 91/PUUXVIII/2022, it will have a good impact on Indonesia's economic recovery. This research is a normative juridical research based on applicable legal sources. This research was analyzed descriptively with a qualitative approach. The results of the research will explain the effectiveness of the Constitutional Court's decision and see its impact on the Indonesian economy.